Lightweight ventilated façade: Acoustic performance in laboratory conditions, analysing the impact of controlled ventilation variations on airborne sound insulation. Issue 4 (December 2020) - Zamora Mestre, Joan Lluis; Niampira, Andrea
The use of double-sheet enclosures with an intermediate non-ventilated air cavity guarantees a higher airborne sound insulation. The insulation advantages depend on air tightness and the placement of sound absorbing material in the air cavity. The lightweight ventilated façade is a system constructed by the addition of an external light cladding on a heavy single wall to establish an intermediate air cavity. This air cavity can be ventilated under controlled cooling effects, because of Sun's radiation, and to reduce the risk of dampness caused by rainwater. Owing to this ventilation, acoustic insulation of the lightweight ventilated façade could be less effective. However, some authors indicate that air cavity moderate ventilation does not necessarily lead to a significant reduction in the airborne sound insulation. The authors previously verified this situation in a real building where the existing façade of masonry walls was transformed into a lightweight ventilated façade. The preliminary results indicate the acoustic benefits can be compatible with the hygrothermal benefits derived from controlled ventilation. This article presents the next step, the evaluation of the lightweight ventilated façade acoustic performance under laboratory conditions to revalidate the previous results and refining aspects as the air cavity thickness or the state of openings ventilation. The main results obtained indicate that the airborne sound insulation in laboratory is aligned with the previous results in a real building. Air cavity thickness from 110 to 175 mm and ventilation openings from 0% to 3.84% of the façade area does not lead to a significant reduction in the airborne sound insulation.